(untitled) (JURNAL BEATITUDES, 2023)
This paper aims to provide an understanding and application of the role of Bible reading activities that should be a habit that is applied by every believer. Because the Bible is God himself, the Word of God written and inspired by his prophets as one of God’s means of speaking to His people. The Bible has a very good impact on human life, especially believers, namely correcting wrong behavior, which deviates from the deeds that God wants His people to do and also specifically in the growth of the faith of believers themselves. If God’s people do not listen to God’s voice, especially in reading the Bible, how will there be a growth of faith in believers. Therefore this is the thing that ST3B students are concerned about in raising this theme in Community Service activities. And this habit should be done from an early age. This activity was carried out at the Damai Sejahtera Orphanage Foundation, which is located at the Tembesi Center, Batu Aji, Batam. The method used by students is to re-teach or re-educate about the importance of reading the Bible every day for every child, especially children in the Damai Sejahtera Orphanage Foundation